0280 A RECIPROCAL RELATIONSHIP BETWEEN SLEEP AND ALZHEIMER'S DISEASE?. (28th April 2017) - Kalinina, J; Brunner, J; Yao, L; Hatcher, NG; Gehrman, PR; Kling, MA; Shaw, LM; Gooneratne, NS; Chahine, LM; Winrow, CJ; Gotter, AL
Abstract: Introduction: Sleep-wake cycling is a vital brain function associated with cognition and synaptic plasticity. An intriguing relationship between sleep and Alzheimer's disease (AD) emerged after an observation that sleep-deprived rodents accumulated β-amyloid (Aβ). In parallel, another study demonstrated that mice lacking the gene encoding wake-promoting orexin neuropeptides (OX-A, OX-B) not only exhibited characteristic hypersomnolence, but also developed half as many Aβ plaques. While not universally observed by research groups, there is also a report showing elevated CSF OX-A in patients with moderate to severe AD. While the exact relationship between sleep and AD remains to be deciphered, the association between OX-A and Aβ warrants further study. Methods: To assess whether humans with insomnia accumulate greater levels of (a) OX-A and (b) Aβ oligomers (AβO) (a neurotoxic species implicated in the pathology of AD), CSF from insomniacs (N=3) and good sleepers (N=3) was mined for OX-A and AβO, using MSD and Singulex ELISA platforms, respectively. CSF levels of other neurotransmitters and metabolites, including acetylcholine, tele -methylhistamine, dopamine, 3, 4-dihydroxyphenyl-acetic acid, homovanillic acid, glutamate and gamma-aminobytyric acid were measured using LC/MS-MS. In a parallel study, the (a) OX-A and (b) AβO levels in the CSF of aged African Green Monkeys (AGM), known to develop Aβ plaques with aging, were compared to young AGM using abovementioned methodologies. Results: Preliminary data indicated a trend towards elevated OX-A and AβO in subjects with insomnia vs. those with good sleep. Furthermore, we also observed a tendency towards elevation of tele -methylhistamine in poor sleepers. Finally, we demonstrate a significant (p=0.0001) increase of baseline CSF oligomers in aged vs. young monkeys, with a parallel, albeit not significant trend for CSF OX-A levels. Conclusion: The reciprocal relationship between sleep and AD remains incompletely understood. The current pilot study strengthens the link between OX-A, Aβ and AD and supports further studies to validate these observations. Support (If Any): None.